2013
DOI: 10.1253/circj.cj-13-0311
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C Prevents Intrauterine Programming of in vivo Cardiovascular Dysfunction in the Rat

Abstract: Background: Fetal hypoxia is common and in vitro evidence supports its role in the programming of adult cardiovascular dysfunction through the generation of oxidative stress. Whether fetal chronic hypoxia programmes alterations in cardiovascular control in vivo, and if these alterations can be prevented by antioxidant treatment, is unknown. This study investigated the effects of prenatal fetal hypoxia, with and without maternal supplementation with vitamin C, on basal and stimulated cardiovascular function in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(84 citation statements)
references
References 64 publications
5
78
1
Order By: Relevance
“…However, it is possible that suppression of NO in the absence of injury could alter vascular tone and oxygen availability leading to ROS production and cell death in otherwise normal tissue. Such negative impacts of altered NO production in the absence of injury have been reported in rodent studies of antioxidant treatment using vitamin C [44][45][46]. As in the current study, these studies did include a no-injury group and reported vascular endothelial dysfunction later in life in offspring exposed to vitamin C in the absence of hypoxia [44][45][46].…”
Section: Potential Adverse Effects Of Wtapc Administration To Uninjursupporting
confidence: 62%
See 1 more Smart Citation
“…However, it is possible that suppression of NO in the absence of injury could alter vascular tone and oxygen availability leading to ROS production and cell death in otherwise normal tissue. Such negative impacts of altered NO production in the absence of injury have been reported in rodent studies of antioxidant treatment using vitamin C [44][45][46]. As in the current study, these studies did include a no-injury group and reported vascular endothelial dysfunction later in life in offspring exposed to vitamin C in the absence of hypoxia [44][45][46].…”
Section: Potential Adverse Effects Of Wtapc Administration To Uninjursupporting
confidence: 62%
“…Such negative impacts of altered NO production in the absence of injury have been reported in rodent studies of antioxidant treatment using vitamin C [44][45][46]. As in the current study, these studies did include a no-injury group and reported vascular endothelial dysfunction later in life in offspring exposed to vitamin C in the absence of hypoxia [44][45][46]. Interestingly, wtAPC decreased astrogliosis in the corpus callosum and cortex irrespective of the mode of birth, despite the effect it had of increasing CD11β-positive and TUNEL-positive cell counts in the c-section controls.…”
Section: Potential Adverse Effects Of Wtapc Administration To Uninjurmentioning
confidence: 74%
“…Several randomized controlled trials have been performed to determine whether antioxidants supplementation in complicated pregnancies are beneficial, showing no evidence that these supplements may prevent preeclampsia (Poston et al, 2006, 2011; Basaran et al, 2010; Roberts et al, 2010; Xu et al, 2010; Conde-Agudelo et al, 2011; Kalpdev et al, 2011; Rumbold et al, 2011; Polyzos et al, 2012). In marked contrast, animal models and few human experiences have shown effectiveness in the use of different antioxidants preventing pregnancy complications and short- and long-term vascular dysfunction during pathologic pregnancies (Richter et al, 2009; Tara et al, 2010; Parraguez et al, 2011; Giussani et al, 2012; Wibowo et al, 2012; Jones et al, 2013; Kane et al, 2013). Nowadays, it is not recommended the use of antioxidants in pregnancy but the debate is still open and it merits new therapeutical approaches as it is clear that oxidative stress is partly determining complications.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that treatment of offspring exposed to prenatal hypoxia with an antioxidant during prenatal or postnatal life prevented cardiac dysfunction (Kane et al . ) and cardiac susceptibility to I/R injury in adult life (Patterson et al . ).…”
Section: Discussionmentioning
confidence: 99%